Effects of nitrogen and salt on growth and physiological characteristics of processing tomato under drip irrigation - Wang, Jiulong; Wang, Zhenhua; Li, Haiqiang; Li, Wenhao; Wang, Tianyu; Tan, Mingdong (International Journal of Agricultural and Biological Engineering, 2021)
Xinjiang of China is one of the three largest planting bases of processing tomato in the world, but soil salinization has restricted the production of tomato processing. In order to study the effects of soil nitrogen, salt and their interaction on growth and physiological characteristics of processing tomato under drip irrigation, different amount of nitrogen fertilizer were added to reconcile different salt stress to explore the response mechanisms of growth and yield of processing tomato to soil nitrogen and salt contents with a two-year experiments. The results showed that the effects of soil salinity on the growth and physiological characteristics of processing tomato were significantly greater than that of input of nitrogen fertilizers. The higher soil salt content (≥5.0 g/kg) significantly inhibited the growth of processing tomato. The increase in addition of nitrogen fertilizer could alleviate the salt inhibition and promote the growth of processed tomato with the increase of soil salt content, and the maximum nitrogen application rate was 300 kg/hm2. The linear plus platform was selected to determine the nitrogen effect models of non-saline-alkali soil and weak saline-alkali soil, but the square root nitrogen effect model of moderate saline-alkali soil was selected to accurately predict the yield of processing tomato. It was suggested the processing tomatoes should be planted in moderate saline-alkali soil to achieve higher yields due to lower input of nitrogen fertilizer, potentially reducing fertilizer costs and maximizing profits from high processing tomato yields. The results have a strong guiding significance for planting of processing tomato on saline-alkali land and appropriate fertilization to increase the yield of processing tomato. Keywords: drip irrigation, processing tomato, salinity, photosynthetic fluorescence parameters, nitrogen use efficiency, water use efficiency DOI: 10.25165/j.ijabe.20211406.6568 Citation: Wang J L, Wang Z H, Li H Q, Li W H, Wang T Y, Tan M D. Effects of nitrogen and salt on growth and physiological characteristics of processing tomato under drip irrigation. Int J Agric & Biol Eng, 2021; 14(6): 115–125.